Evolve or die - "Gates, Phil" (Scholastic London, 2008)
Why are mutating mosquitoes humankind's worst enemy? Which dinosaurs let loose some deafening farts? Why do rabbits eat their own poo? Get the awful answers to those queasy questions in this horrible book of science